2017
DOI: 10.3791/55044
|View full text |Cite
|
Sign up to set email alerts
|

Light Sheet Fluorescence Microscopy of Plant Roots Growing on the Surface of a Gel

Abstract: One of the key questions in understanding plant development is how single cells behave in a larger context of the tissue. Therefore, it requires the observation of the whole organ with a high spatial-as well as temporal resolution over prolonged periods of time, which may cause phototoxic effects. This protocol shows a plant sample preparation method for light-sheet microscopy, which is characterized by mounting the plant vertically on the surface of a gel. The plant is mounted in such a way that the roots are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…Analysis of heterogeneity of T in sister cells within the maize RAM showed they do not vary by more than 15-20 % (Ivanov, 1971). Recent time-lapse studies in arabidopsis showed that variation in sister cell T averaged 8.3 % (von Wangenheim et al, 2017b; data extracted from their Video 3, n = 6 sister groups). Another source of heterogeneity is that some cell types (metaxylem in monocots) stop proliferating earlier, but the fraction of these cells is also not significant.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of heterogeneity of T in sister cells within the maize RAM showed they do not vary by more than 15-20 % (Ivanov, 1971). Recent time-lapse studies in arabidopsis showed that variation in sister cell T averaged 8.3 % (von Wangenheim et al, 2017b; data extracted from their Video 3, n = 6 sister groups). Another source of heterogeneity is that some cell types (metaxylem in monocots) stop proliferating earlier, but the fraction of these cells is also not significant.…”
Section: Discussionmentioning
confidence: 99%
“…However, embedding of plant aerial parts is not compatible with proper physiological conditions, which are necessary for long-term imaging. Recently developed open systems for plant preparation and maintenance during LSFM long-term imaging von Wangenheim et al, 2017) ensure that plants are maintained in the microscope vertically oriented (according to the gravity vector). Simultaneously, continuous root growth is supported by appropriate culture medium, and the aerial part grows freely in the air.…”
Section: Lsfmmentioning
confidence: 99%
“…While perfusion systems will remain the method of choice for wash-out experiments, the imaging chamber has been used successfully for the administration of dexamethasone 12 and other compounds. One note, while this article was in preparation von Wagenheim and colleagues 18 described a chamber for imaging lateral root development using light-sheet microscopy.…”
Section: Discussionmentioning
confidence: 99%